Pengembangan Struktur Kanopi bagi Usaha Sumber Sehat sebagai Upaya Peningkatan Fasilitas di Desa Sukaraya - Siahaan, Sihar; Subhan, Muhammad Ari; Ekinola, Efri Debby (INTAN CENDEKIA (Jurnal Pengabdian Masyarakat), 2023)
The Community Partnership Program (PKM) is one of the means of service to express ideas in dealing with problems that arise in the community. We propose this PKM with the aim of helping MSMEs who are having difficulties in developing their businesses. One of these MSMEs is located in Sukaraya Village, Hamlet Amal with a trade name, namely Sumber Sehat which is a target source for PKM implementation partners which can be categorized as an economically productive community. The problems faced by healthy resource partners are inconvenient places to live, such as leaky and rickety zinc canopies, wooden poles that are porous due to being eaten by termites and slanted poles and cement floors and do not have sales management. These SMEs sell food items such as chicken, carp, catfish, eel, tilapia and vegetables. Therefore, the purpose of this service is to help partners to repair canopies and poles that are no longer functioning properly. The target to be achieved in this PKM is that the place to trade these materials can become a comfortable place for consumers. The solution given to solve the problem to achieve the target, then repair the trading place. Partners really hope that their trading place can be repaired and is suitable for reuse as before. By providing canopy assistance and management of healthy sources of business, it is possible for partners to be able to sell community food by having a comfortable and safe trading place. At the time of making the canopy and training in business management, the community was very welcoming, and hoped that the community service partnership could continue in the future